Estudo comparativo da função e qualidade de vida de pacientes submetidos a artroplastia total de joelho com plataformas tibiais fixa e móvel - Nacca, Daiane Cavenaghi [UNIFESP] (2016)
Introduction: The knee osteoarthritis is characterized by degeneration of articular cartilage and subchondral bone, being a major cause of pain, functional disability and lost of quality of life in the elderly. The surgical total knee arthroplasty may be used in the treatment of elderly patients with advanced stages of degenerative joint disease, with the purpose to lessen the pain, to improve the function and gain of quality of life in this population. They can be divided, according to the tibial component, into two types: total arthroplasties with a fixed tibial platform and mobile tibial platform. Objective: This is a prospective randomized study that aims to compare the function and quality of life of patients who underwent total knee arthroplasty with fixed tibial platform and mobile tibial platform. Methods: We evaluated 240 patients with knee osteoarthritis. Patients eligible by inclusion and exclusion criteria were randomized into two groups - Group A consisted of 120 patients who underwent total knee arthroplasty with fixed tibial platform and the B group of 120 patients who were submitted to arthroplasty with mobile platform. Patients were evaluated according to the function and quality of life by validated questionnaires for Portuguese-speaking WOMAC and SF-36, and pain scores by Visual Analog Scale of Pain, preoperatively and at 6 months, 1 year, 2 years, 4 years and 8 years of surgery. Results: With regard to the various domains of the SF-36 we can see that the average behavior of functional capacity scores, physical aspects, pain and emotional aspects in the patient groups were statistically different during follow-up (p <0.05 interaction). The other domains of quality of life showed no mean differences over whether the group follow-up (p >0.05) and only the social aspects differ among the groups independent of time points (p = 0.023). We can also observe that with both prostheses, there was an increase in quality of life scores for preoperative pain for the other moments (p <0.05). But with two years of surgery, the mean score of domino pain of the SF-36 of the patients who did mobile prosthesis it was statistically higher than the patients who fixed prosthesis (p <0.001). With respect to pain assessed by VAS and pain scores, function and stiffness WOMAC, we can see that showed an average change over following in both patient groups (p <0.001), with no difference between the types of prosthesis at any time of the evaluation. We can also observe that there was a worsening of function score of 2 to 4 years and from 4 to 8 years in both groups. (P <0.001). Conclusion: With eight years of follow-up we observed no clinically significant differences in function and quality of life in patients who underwent total knee arthroplasty with fixed or mobile tibial platform. However, with two years postoperatively we noticed that the pain scores in quality of life were lower in the group with fixed platform.